On quality and variety bias in aggregate prices - Zanetti, F; Hamano, M (Wiley, 2018)
How do product variety and quality affect the aggregate price bias? We develop a general equilibrium model that accounts for the joint interaction of product quality and variety. Our findings show that the aggregate price bias is pro-cyclical and the contribution of product variety is persistent whereas the contribution of product quality becomes counter-cyclical in the medium to long run. We show that accounting for product quality and variety has critical implications on the measure of cyclical fluctuations. Measurements of cyclical fluctuations derived using the consumption deflator, which abstracts from changes in product quality and variety, underestimate the variables' true volatility.